Sarcoidosis With Multisystem Lesions: A Review of the Literature. Issue 2 (May 2015) - Sun, Wen-Ping; Li, Mei; Sun, Zhen-Kui; Li, Ming-Hua; Li, Yong-Dong; Zhu, Yue-Qi
Abstract : Sarcoidosis is a chronic multisystemic inflammatory disease that is characterized by noncaseous epithelioid cell granulomas infiltration of all affected tissues. Sarcoidosis generally involves the lungs, neurological system, lymphatic system, and the skin. However, this disease has a broad spectrum of clinical manifestations, and hence it is difficult to make a clear diagnosis. The diagnosis is usually based on radiographic findings of the mediastinal and hilar lymph node swelling. The male genitourinary tract is rarely affected, and testicular with epididymal lesions are rare. This case report documents radiographic imaging and pathologic features in a patient with sarcoidosis with extensive multisystem involvement.